The Effectiveness of Using the Flipped English Classroom (Fec) Strategy at Eleven Grade UPT SMA Negeri 17 BONE - Astiani; Syatriana, Eny; Firman (FKIP Unismuh Makassar, 2020)
This study aims to determine the effectiveness of using the Flipped English Classroom strategy to improve students' reading comprehension skills in the eleventh grade of UPT SMA NEGERI 17 BONE. This research is pre-experimental, with a one-group pre-test post-test research design. The population of this research is 11th-grade students of UPT SMA NEGERI 17 BONE consisting of 6 classes, each of 22-27 students. The sample of this study was 22 students who were selected using the purposive sampling technique. The instruments used are pre-test and post-test. The results of this study indicate that the use of the Flipped English Classroom (FEC) learning strategy is effective in improving students' reading comprehension skills. This is proven by the students' mean scores on the Pre-Test and Post-Test. The mean score of students on the Pre-Test or before treatment shows a value of 30.68, while after being given treatment or Post-Test showed a value of 45.45. other than that, the value of Sig. (2-tailed) indicates a value of 0.001 with a Sig level value. (2-tailed) 0.05 (5%). It can be concluded that Sig. (2-tailed) 0.001 < 0.05 means that H0 is rejected and Ha is accepted. In conclusion, this proves that the Flipped English Classroom (FEC) Strategy effectively improves students' reading comprehension skills.